Green Synthesis of Silver Nanoparticles Using Saussurea Costus Methanolic Extract: A Novel Strategy against Multidrug-Resistant Listeria Monocytogenes - Sabri, Mustafa Emad; Hasan, Hayfaa Jumaah (American Journal of Biomedicine and Pharmacy, 2025)
The rising prevalence of multidrug-resistant (MDR) Listeria monocytogenes in dairy products necessitates innovative control strategies. This study investigated green-synthesized silver nanoparticles (AgNPs) using Saussurea costus methanolic extract against MDR L. monocytogenes from 200 dairy samples (100 raw buffalo milk, 100 local cheese) in Al-Diwaniyah City, Iraq. Isolation involved selective enrichment and chromogenic agar plating, with confirmation via biochemical tests (catalase, beta-hemolysis) and PCR detection of virulence genes (16S rRNA, Ami, Vip). Results revealed 16.5% prevalence (23% milk, 10% cheese; p=0.013). All isolates exhibited MDR, showing complete resistance to aminoglycosides, penicillins, tetracyclines, and cephalosporins, while remaining susceptible to macrolides, carbapenems, and fluoroquinolones. GC-MS analysis identified dehydrocostus lactone (41.52%) as the primary phytoconstituent. AgNPs were successfully synthesized, demonstrating a characteristic UV-Vis peak at 435 nm. FESEM confirmed spherical morphology (76.45±1.32 nm), while FTIR and XRD verified phytochemical capping and crystalline structure. Antibacterial assays showed dose-dependent inhibition, with methanolic AgNPs exhibiting superior activity (22±1.1 mm zone at 100 mg/mL) compared to crude extract (10±0.5 mm). Statistical analysis confirmed significant differences (ANOVA, p<0.001), with strong dose-response correlation (R²=0.99). These findings highlight S. costus-mediated AgNPs as a potent, eco-friendly alternative against MDR L. monocytogenes, offering promising applications in food safety. Further studies should explore large-scale synthesis and in vivo efficacy.